The Impact of Musical Competence on Working Memory and Speech-in-Noise Performance - Yoshita Sharma; Harshada Mali; Divya Chauhan; Kavassery Venkateswaran Nisha (Auditory and Vestibular Research)
Background and Aim: The concept of Musical Competence (MC) encompasses a unique amalgamation of innate aptitude and cultivated skill, encompassing elements of formal training, informal practice, and real-time musical performance. While musical attitude and training influence speech processing abilities and Working Memory (WM), the study examines whether the self-perceived MC plays any role in these processes. This study aimed to investigate whether an individual’s self-perceived MC has an impact on their WM, Speech Perception in Noise (SPIN), and Listening Effort (LE) abilities. Methods: A non-experimental, standard group comparison research design was employed. Various cognitive tasks, including WM tests, SPIN, and National Aeronautics Space Administration-Task Load Index (NASA-TLX), are administered to gauge different skills within groups.59 musicians were categorized into high self-perceived MC (MChigh) and low self-perceived MC (MClow), as assessed on scores of Edinburgh lifetime musical experience questionnaire, were evaluated for their WM and SPIN abilities. Results: Mann Whitney U test was carried out to find group differences, while Fisher Discriminant Analysis (FDA) was performed for group membership prediction. MChigh scored significantly greater scores WM and SPIN scores than MClow, but there were no significant group differences in LE. Cognitive tasks effectively distinguish between groups. Fisher discrimination analysis confirmed the predictive value of tasks like 2n-back and backward-span in group differentiation. Conclusion: This study underscores potential cognitive and auditory processing benefits derived from the self-belief of musicians. Musicians with higher MC exhibit enhanced cognitive skills, particularly in WM tasks and auditory processing.